(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
During the Second World War, the Soviet Union demonstrated remarkable superiority in the production of military weapons, establishing itself as a formidable military force on the Eastern Front. Through a combination of industrial capacity, technological innovation, strategic planning, and foreign support, the USSR outproduced its adversaries and maintained a steady supply of weapons and equipment. The rapid industrialization under Joseph Stalin’s regime, coupled with efficient resource allocation and coordination between military and industrial sectors, enabled the Soviet Union to mass-produce essential military equipment, including tanks, aircraft, artillery, and small arms. This industrial prowess played a crucial role in the eventual Allied victory over the Axis powers.